(untitled) (Altre Modernità, 2016)
In 2009, Joyce Carol Oates published the collection of short stories Dear Husband, which contained the eponymous story inspired by the case of Andrea Yates, a Texan housewife who had killed her five children in the house bathtub in 2001. The woman, who was sectioned in 2007, declared that hers had been “a mother’s final act of mercy”, as she had meant to save her children from the devil. She had been suffering from post-partum psychosis, a condition that made it hard to judge whether she was aware of what she was doing while drowning her kids. The essay analyzes the depiction that Oates made of Yates in her short story, and considers the treatment that the author reserved to her character: is she portrayed as a villain or a victim? With the help of Paul Ricoeur’s concepts of “guilt” and “impurity”, and a comparison between the actuality of the Yeats case and its fictional counterpart, it will be possible to understand the point of view of the author on the culpability of Andrea Yates.